Era Baru Kesehatan Mental Indonesia: sebuah Kisah dari Desa Siaga Sehat Jiwa (DSSJ) - Alifa Syamantha Putri; Moya A.D. Martiningtyas; Afrina E.S. Br. Sagala; Gartika Nurani Erawan; I Putu Ardika Yana; Sarita Matulu; Sustriana Saragih; Niken Kitaka Sari; Nadia Ihsana Ferhat; Patricia Meta Puspitasari; Yova Tri Yolanda; - Subandi (Jurnal Psikologi, 2013)
Due to the large number of people with mental illness in Indonesia, traditional treatment to individuals with mental disorder becomes less effective. Community-based mental health treatment becomes a more effective and efficient choice in handling the disorder. Desa Siaga Sehat Jiwa (DSSJ, Mental Health Awareness Village) has comes as a form of community-based mental health treatment. One of villages in Yogyakarta where the program has been being implemented is in Selomartani village, Kalasan Sub-district, Sleman Regency. This study aimed to look at the process of formation, implementation and obstacles of the program in this village, and to provide advice or suggestions for its improvement. This study used a qualitative approach with narrative method. Data were retrieved through interviews and focus group discussions. Participants involved in the study were 19 cadres of the program. Results obtained from the study indicated that cadres have ability in understanding clearly the system and their roles in the program and they know the consequences of being a cadre of DSSJ. The new finding obtained during the research process was the emergence of "compassion fatigue” or “secondary traumatic stress", a traumatic disorder suffered by the cadre while handling patients. Keywords: community-based mental health, compassion fatigue, Mental Health Awareness Village